Ultrastructural Description of Breviata anathema, N. Gen., N. Sp., the Organism Previously Studied as "Mastigamoeba invertens" - WALKER, GISELLE; DACKS, JOEL B.; MARTIN EMBLEY, T. (The Journal of eukaryotic microbiology, 2006)
An understanding of large‐scale eukaryotic evolution is beginning to crystallise, as molecular and morphological data demonstrate that eukaryotes fall into six major groups. However, there are several taxa of which the affinities are yet to be resolved, and for which there are only either molecular or morphological data. One of these is the amoeboid flagellate Mastigamoeba invertens. This organism was originally misidentified and studied as a pelobiont using molecular data. We present its first light microscopical and ultrastructural characterisation. We demonstrate that it does not show affinities to the amoebozoan pelobionts, because unlike the pelobionts, it has a double basal body and two flagellar roots, a classical Golgi stack, and a large branching double membrane‐bound organelle. Phylogenetic analyses of small subunit ribosomal RNA suggest an affinity with the apusomonads, when a covariotide correction for rate heterogeneity is used. We suggest that previous molecular results have been subject to artefacts from an insufficient correction for rate heterogeneity. We propose a new name for the taxon, Breviata anathema; and the unranked, apomorphy‐based name “Breviates” for Breviata and its close relatives.